ANALISIS KEEKONOMIAN PERANCANGAN PLTS TERAPUNG DAN PLTMH DI BENDUNGAN SIDAN - Dwi Gayatri, Ayunda; Dwi Giriantari, I.A.; Jati, I K. (Program Studi Teknik Elektro UNUD, 2024)
The target of using new and renewable energy (EBT) in Indonesia is still to reach the target set at 23% by 2025. The design of Floating PLTS and PLTMH at the Sidan Dam is one thing to maximizing the use of New Renewable Energy, especially in BaIi Province. Therefore, carbon emission analysis and economic analysis on the design of Floating SoIar Energy Power PIant and MycroHydro power plants are carried out. The capacity of the Floating Solar Power Plant utilizes 5% of the dam water level of 1.4 MW and the capacity of the MycroHydro power plants is 0.29 MW. The Floating Solar Power Plant and MycroHydro power plants designed have an investment cost of IDR 22,239,823,399 and IDR 2,739,517,355. Economic analysis of Floating Solar Power Plant is based on NPV of IDR 3,414,844,329, PI of 1.15, and PP of 16.86 years. The economic analysis of MycroHydro power plants is based on NPV of Rp 16,759,312,607, PI of 7.12 and PP of 2.16 years. Reduction in carbon emissions in 25 years for Floating Solar Power Plant amounted to 336,015 tons of CO2e and for MycroHydro Power Plants amounted to 503,548 tons of CO2e.